The Legality of Oil & Gas Production Sharing Contract Gross Split Scheme - Sugiyartomo, Fakharsyah Hanif (Purnomo Yusgiantoro Center, 2019)
As an oil producing nation, Indonesia embodied its authority to manage its oil resources through article 33 paragraphs 3 of The Republic of Indonesia Constitution 1945. Regarding the article, this means that the state has the authority to manage Indonesian natural resources, directly or indirectly, through other public and/or private institutions and the profit of such activity shall be for the benefit of the people. This granted the state to appoint other institution, including a National/International Oil Company (NOC/IOC), to manage the exploration and production of oil, as that particular activity is regarded as a high risk and high capital business. In order to do so, according to Law no. 22 2001, the state may appoint a NOC/IOC through a production sharing contract. In this research, it is founded that the regulation that governed a production sharing contract with the gross split mechanism—Ministry of Energy and Mineral Resources Regulation No. 8 2017 jo. Ministry of Energy and Mineral Resources No. 52 2017—does not have a strong legal basis. In overall, the management of oil and gas through the gross split mechanism does not gives a maximum benefit for the state, and does not attract the IOC/NOC interest to explore and produce oil and gas in Indonesia. Therefore, in this paper, the reviewing of oil and gas management through a gross split mechanism is recommended.